2013
DOI: 10.1017/s0001924000008587
|View full text |Cite
|
Sign up to set email alerts
|

Aerothermodynamics of a hypersonic projectile with a double-disk aerospike

Abstract: The use of aerospikes at the nose of a hypersonic vehicle can substantially reduce its drag; however, the associated heat flux at the reattachment point is very high for turbulent flows. In this paper, the aerothermodynamics of a generic projectile model represented by a hemisphere-cylinder, fitted axisymmetrically with an aerospike at the nose is investigated numerically with a commercially available Navier Stokes Solver. The base model is a hemisphere-cylinder with a diameter of 40mm and an overall length of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The effects of the spike length, shape, spike nose configuration and angle of attack on the reduction of the drag were experimentally studied by Kalimuthu et al [25], and they found that the aerodisk with L/D = 2.0 is most effective among the models tested. Yadav and Guven [26] proved numerically that double-disk aerospikes are superior to single disk aerospikes of same overall length and hemispherical cap size in reducing drag of the main body. To study the aerodynamic characteristic of spike at a certain angle of attack, Schülein [27] introduced the concept of "pivoting spike" in which the spike is maintained aligned with the freestream direction while the whole body is at incidence.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of the spike length, shape, spike nose configuration and angle of attack on the reduction of the drag were experimentally studied by Kalimuthu et al [25], and they found that the aerodisk with L/D = 2.0 is most effective among the models tested. Yadav and Guven [26] proved numerically that double-disk aerospikes are superior to single disk aerospikes of same overall length and hemispherical cap size in reducing drag of the main body. To study the aerodynamic characteristic of spike at a certain angle of attack, Schülein [27] introduced the concept of "pivoting spike" in which the spike is maintained aligned with the freestream direction while the whole body is at incidence.…”
Section: Introductionmentioning
confidence: 99%
“…Further, in order to reduce the amount of drag reduction for the spiked body configuration with a spike of length beyond the critical length (L/D=2.0), an intermediate aerodisk is mounted on the spike stem. The geometry of the intermediate aerodisk used in the present investigation is adopted with reference to the aerodisk used by Yadav et al [15][16]. The point of flow separation over the spike length for longest spike (L/D=2.0) has been considered as the location of mounting the intermediate aerodisk.…”
Section: Geometrymentioning
confidence: 99%
“…This reduces the level of the surface pressure and hence a reduction in drag coefficient in obtained. Recently, Yadav et al [15][16] using computational studies reported an even further increase in the amount of drag reduction at hypersonic flow by mounting a series of aerodisk along the spike stem in comparison to a single aerodisk mounted spiked body configuration. In addition to the spiked blunt bodies, numerous studies have also been conducted involving the investigation of the aerodynamic forces over more streamlined bodies (Cone and Ogive) without mounting any spike [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The flat faced disk has a larger structural strength than hemispheric disk because of its geometric shape at the cruise angle, ensuring its durability under heavy lateral loads, also reduces elastic deformation at hypersonic speeds. [7] showed that the drag of the vehicle nose is remarkably influenced by the disk shape, and [18] suggested that the use of double-disk aerospike can favourably reduce drag, considering from the aspect, SFF and DFF with appropriate disk shape and position, shown in Fig. 2(b) and (c), are added in the research to compare with the hemispheric disk in order to carry out the disk shape selection.…”
Section: Effects Of Disk Shape On Dragmentioning
confidence: 99%